UVB Induced Skin Cancer Development in Experimental Mouse Model : A Review - Muhammad Wahizul Haswan, Abdul Aziz; Dayang Fredalina, Basri; Siti Fathiah, Masre; Ahmad Rohi, Ghazali (Penerbit UTM Press, 2023)
Skin cancer is a widespread global issue, with ultraviolet (UV) radiation being a significant risk factor. Researchers often use the mouse skin cancer model to develop novel therapeutic chemoprevention strategies. This model involves exposing mice to UVB radiation to induce skin arcinogenesis. In this short communication, we found that 69.57% of studies used female SKH-1 hairless mice, 17.39% used BALB/c mice, 8.69% used Swiss albino mice, and 4.35% used HRS/J hairless mice. All studies used mice aged 5-8 weeks. Different models of mice were exposed to varying doses of UVB radiation. SKH-1 hairless mice received UVB radiation twice a week for 10-18 weeks, while Swiss albino mice were exposed to UVB radiation three times a week for 30 weeks. HRS/J hairless mice received UVB radiation five times a week for 15 weeks. BALB/c mice were treated with DMBA and exposed to UVB radiation for 10-16 weeks to induce skin tumors. However, using SKH-1 hairless mice is costly. In conclusion, we can suggest BALB/c mice treated with DMBA and exposed to UVB radiation three times a week for 16 weeks for UVB-induced skin cancer model, as it is more cost-effective than other hairless mouse models.